TRANSLATION STRATEGY OF ONOMATOPOEIA IN "9 LIVES" WEBTOON FROM ENGLISH TO INDONESIAN - Ramadhan, Farhan; Sinaga, Inta Masni; Noryatin, Yeni (Jurnal Bahasa Asing, 2025)
This research aims to identify the types of onomatopoeia in the 9 Lives Webtoon and to determine the translation strategies used by the translator during the analysis. This study adopted a qualitative approach, with data collected by reading and classifying words containing different types of onomatopoeia and translation strategies in the 9 Lives Webtoon. In conducting this research, the researcher applied theories from Bredin for types of onomatopoeia and Baker for translation strategies. As a result of the data interpretation, three types of onomatopoeia were identified in the Webtoon: 17 instances of direct, 8 associative, and 5 exemplary types. Regarding translation strategies, there were 22 cases of cultural substitution, 5 of a loan word or loan word plus explanation, and 3 of paraphrasing using related words.